1982
DOI: 10.1073/pnas.79.8.2549
|View full text |Cite
|
Sign up to set email alerts
|

Junction between Z and B conformations in a DNA restriction fragment: evaluation by Raman spectroscopy.

Abstract: Raman vibrational spectra were obtained from two DNA restriction fragments and the DNA polymer (dGdC)n-(dG-dC)n in 0.01 and 4.5 M NaCl. One fragment contained 95 base pairs (bp) of the Eschelrichia coli lactose operator-promoter region (95-bp fragment). The other fragment consisted of the 95-bp region flanked by 26 and 32 bp ofdC-dG sequences and BamHI ends (157-bp fragment). In 0.01 M NaCl all three DNAs have Raman spectra characteristic of a right-handed B conformation. The high salt spectrum of the 95-bp f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Based on their sensitivity to S1 nuclease Singleton et al, 1984) and chemical reagents, like hydroxylamine, OsO 4 and dimethyl sulfate (Johnston and Rich, 1985;Johnston, 1992), the sites between right-handed B-DNA and left-handed Z-DNA were reported to undergo considerable structural alterations during the transition of alternating purine/pyrimidine (APP) sequences from B-to Z-DNA conformation under torsional stress. Together with the results of Raman spectroscopy studies (Wartell et al, 1982), these data proved the B-Z junctions to represent unusual, distorted DNA structures whose exact conformation is still unknown, but which is, to a certain extent, apparently single-stranded in nature (Sheardy, 1988;Lu et al, 1992). The detection in the present study of S1 nuclease-and OsO 4 /bipyridine-sensitive nucleotides at the boundaries of d(GT) 17 as well as of perfect and interrupted d(CG) 17 tracts provided an additional hint that the APP sequences had indeed adopted Z-DNA conformation, with the generation of B-Z and Z-Z junctions (Johnston et al, 1991), after their insertion into supercoiled vector DNA.…”
Section: Interaction Of Cif Proteins With Supercoiled Plasmids Contaimentioning
confidence: 82%
“…Based on their sensitivity to S1 nuclease Singleton et al, 1984) and chemical reagents, like hydroxylamine, OsO 4 and dimethyl sulfate (Johnston and Rich, 1985;Johnston, 1992), the sites between right-handed B-DNA and left-handed Z-DNA were reported to undergo considerable structural alterations during the transition of alternating purine/pyrimidine (APP) sequences from B-to Z-DNA conformation under torsional stress. Together with the results of Raman spectroscopy studies (Wartell et al, 1982), these data proved the B-Z junctions to represent unusual, distorted DNA structures whose exact conformation is still unknown, but which is, to a certain extent, apparently single-stranded in nature (Sheardy, 1988;Lu et al, 1992). The detection in the present study of S1 nuclease-and OsO 4 /bipyridine-sensitive nucleotides at the boundaries of d(GT) 17 as well as of perfect and interrupted d(CG) 17 tracts provided an additional hint that the APP sequences had indeed adopted Z-DNA conformation, with the generation of B-Z and Z-Z junctions (Johnston et al, 1991), after their insertion into supercoiled vector DNA.…”
Section: Interaction Of Cif Proteins With Supercoiled Plasmids Contaimentioning
confidence: 82%
“…For a long stretch of alternating purine/pyrimidine tracts found in human fetal globin gene intervening sequences, 20 bp or more of the flanking sequences has been reported to be sensitive to direct nuclease S1 digestion (18). Raman spectroscopy studies showed that the Z conformation can distort the structure of the neighboring region (23). On the other hand, previous chemical analyses of the B-Z junction revealed that the junctions are relatively tight, well-defined structures.…”
Section: Discussionmentioning
confidence: 99%
“…and O-C-C-N symmetric stretching -phospholipids [39] 919 X X X X* C-C stretching of α-glycosidic conformation [39,43]; NH 2 + COOH -proteic clustering [37]; C-COO stretching [43] 1006 X Ring breathing -phenylalanine and tryptophan [38,42,44] 1065 X X C-C stretching of saturated fatty acids, sensible to the acyl chain in lipids [43,45] 1086 X X C-O and C-C stretching of saccharides; C-C stretching of unsaturated fatty acid [43] 1128 X X X X C-N stretching -proteins [44]; C-O and C-C stretching of C-C 6 H 5 stretching of tryptophan and phenylalanine [38,42,44] 1249 X Amide III -deformation C-H and N-H and C-N, C-C and C-O stretching -proteins [47,48] 1266 X X Carbohydrates [39]; CH bending of oleic acid [45] 1304 X X CH 2 bending of fatty acids [43,45] 1342 X X Amide III (C-H, N-H and C-N modes) and C-C and C-O stretching -proteins [47,48]; CH deformationsaccharides (1356 cm -1 ) [39] 1438 X X CH 2 deformations -lipids [38,45] 1452 X CH 2 scissoring -proteins [47,48] 1470 X CH 2 deformation -carbohydrates [39] 1560 X X Tryptophan [36,37]; C-N stretching, NH deformation of amide II -proteins; C=C stretching of tyrosine [46,47];…”
mentioning
confidence: 99%
“…acid Assignment 648 X C-C twisting -phenylalanine; C-H stretching -cysteine [36] 759 X NH 2 + COOH protein clustering -tryptophan [37] 831 X O-P-O asymmetric stretching -tyrosine [36,37] 859 X X X Tyrosine [38]; C-O-C of monosaccharide ring [39,40]; C-C-N symmetric stretching -lipids (877 cm -1 ) [41] 882 X X X X* Tryptophan aromatic ring [42] and phosphate (PO 4 ) [36];…”
mentioning
confidence: 99%
See 1 more Smart Citation